THE INFLUENCE OF MARKET ORIENTATION, ENTREPRENEURIAL ORIENTATION, AND SOCIAL MEDIA MARKETING ON THE MARKETING PERFORMANCE OF SMEs - Effi Indriana; Renea Shinta Aminda; Ahmad Juwaini (SEAN Institute, 2023)
This study aims to analyze the impact of market orientation, entrepreneurial orientation, and social media marketing on the marketing performance of SMEs that are members of ISMEA. The research conducted is quantitative research. The research population consists of 200 ISMEA members, and the sample size is 67 respondents. The research instrument used is a questionnaire. The analysis results use multiple regression techniques. The F-test results show a significance value of 0.000 < 0.05, and the calculated F-value is 52.374 > the tabled F-value of 3.134. This indicates that the alternative hypothesis is accepted. It means that, simultaneously, market orientation, entrepreneurial orientation, and social media marketing have an influence on marketing performance. The t-test results (partial) show a significance value for the influence of market orientation of 0.151 < 0.05, and the calculated t-value is 1.855 > the tabled t-value of 1.67. This indicates that the alternative hypothesis is accepted. It means that market orientation has a significant influence on marketing performance, and the value for entrepreneurial orientation is 0.0391 > 0.05. Therefore, the alternative hypothesis is accepted. This indicates that entrepreneurial orientation has a significant influence on marketing performance. The t-test results (partial) show that the influence of social media marketing on marketing performance has a calculated t-value of 1.972 > the tabled t-value of 1.67. Therefore, the alternative hypothesis for social media marketing is accepted. It means that there is an influence between social media marketing and marketing performance.